Pengaruh perceived ease of use, perceived usefulness, perceived risk, dan price discount terhadap keputusan pembelian menggunakan Shopee Paylater dengan brand image sebagai variabel moderasi pada Generasi Z - Herlin, Ingga; Widoatmodjo, Sawidji (Universitas Tarumanagara, 2024)
This study aims to analyze the influence of perceived ease of use, perceived usefulness, perceived risk, and price discount on purchasing decisions using Shopee Paylater with the brand image as a moderating variable in Generation Z. This study is descriptive with quantitative analysis of Generation Z aged 17-27 years old who has used Shopee Paylater in the Jabodetabek dan Luar Jabodetabek area. Using a purposive sampling technique, samples were collected in a non-probability manner. Questionnaires were distributed to collect data and then processed and analyzed using SmartPLS version 3.0. Likert scale indicators. The study findings show that perceived ease of use, perceived usefulness, perceived risk, price discount, and brand image have a positive and significant influence on purchasing decisions using Shopee Paylater. Not only that, but the brand image can also mediate the impact of perceived ease of use, perceived usefulness, perceived risk, and price discounts on purchasing decisions using Shopee Paylater. Studi ini bermaksud guna menganalisis pengaruh perceived ease of use, perceived usefulness, perceived risk, dan price discount terhadap keputusan pembelian menggunakan Shopee Paylater dengan brand image sebagai variabel moderasi pada generasi Z. Studi ini bersifat deskriptif dengan analisis Kuantitatif terhadap generasi Z dengan usia 17-27 tahun yang pernah menggunakan Shopee Paylater di daerah Jabodetabek dan Luar Jabodetabek. Dengan menggunakan teknik purposive sampling, sampel dikumpulkan dengan cara non-probabilitas. Kuesioner disebarkan untuk menjaring data, yang selanjutnya diolah dan dianalisis menggunakan SmartPLS versi 3.0. Indikator skala Likert. Temuan studi memperlihatkan bahwasanya perceived ease of use, perceived usefulness, perceived risk price discount, dan brand image berpengaruh positif dan signifikan keputusan pembelian menggunakan Shopee Paylater. Tak hanya itu, brand image juga bisa memediasi pengaruh perceived ease of use, perceived usefulness, perceived risk, dan price discount terhadap keputusan pembelian dengan menggunakan Shopee Paylater.